Division of Power in the Formation of Laws After Amendments to the Constitution - Anis Fauzan; Renofadli Rizkiansyah; Kaharuddin; Wicipto Setiadi (CV. Akira Java Bulu, 2025)
This paper will be divided into four parts. First, the introduction section that describes the background in the form of changes to the 1945 Constitution as a paradigm shift in relations between state institutions in Indonesia. Then continued with a brief review of the concept of division of power in a state of law. This first section is then closed with a description of the division of power in the formation of laws before the amendment to the 1945 Constitution. Second, the discussion section entitled the division of power in the formation of laws after the amendment to the 1945 Constitution. This section describes the process of forming laws after the amendment to the 1945 Constitution, which transferred power from the executive to the legislative. Third, the analysis section that contains criticism of the power to form laws after the amendment to the 1945 Constitution. Fourth, the closing section that contains conclusions and suggestions as an outlet in answering the challenges of the need for renewal of Indonesian Constitutional Law related to the division of power in the formation of laws in Indonesia.